Analysis of impurity doping in tunnel junction grown on core–shell structure composed of GaInN/GaN multiple-quantum-shells and GaN nanowire. (22nd December 2021) - Sone, Naoki; Jinno, Daiki; Miyamoto, Yoshiya; Okuda, Renji; Yamamura, Shiori; Jinno, Yukimi; Lu, Weifang; Han, Dong-Pyo; Okuno, Koji; Mizutani, Koichi; Nakajima, Satoru; Koyama, Jun; et al.
Abstract: This study aimed to investigate and analyze the impurity doping characteristics in tunnel junctions (TJs) grown on core–shell structures, comprising GaInN/GaN multiple-quantum-shells (MQSs) and GaN nanowires. To this end, the impurity, structural, and electrical properties of the samples were characterized by scanning electron microscopy, scanning transmission electron microscopy, atom probe tomography (APT), nanoscale secondary ion mass spectrometry (NanoSIMS), and electroluminescence of the device which was fabricated for a prototype laser device to demonstrate an electrical operation of the MQSs layer. From the experimental results of NanoSIMS and APT, we demonstrated that the Mg-related problems in the TJ, such as the diffusion to the n ++ -GaN layer from the p + -GaN layer and formation of clusters in p + -GaN, are critical. Consequently, they cause a high operating voltage and dot-like spot emission of the light-emitting device. Based on the analysis, we suggested remedies and strategies to further improve the TJs that work well.